Effect of Bending and Straightening to the Strength of Reinforcement Steel Bar - Ikhwan, Kana Sabatul; Dalil, M. (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2015)
One of reinforcement bar treatment during delivery transportation is to bend up or buckle in the middle of the bar. This treatment will undermine the strength of the reinforcement bar on buckle region due to its mechanical properties have been changed and no longer within specification. An important point of this study is to knowing the rate of change of mechanical properties, especially strength. Concrete reinforcing steels are bent with nine variations of the bending angle starting from the angle (a) of 20°, 40°, 60°, 80°, 100°, 120°, 140° 160°, and 180°. The data obtained indicated that the yield strength and ultimate tensile strength increases and decreasing the ductility. The increasing percentage of the yield strength is 14% and the tensile strength is 7%. The maximum decreased elongation is 13.42% (a = 180º) from 24.67% (a = 0º) and the reduction of area is decreasing 1.93 %.